Respuesta :

Answer:

Step-by-step explanation:

The system of equations is given as

y=x^2-5x+7 - - - - - - - - - - 1

y=2x+1 - - - - - - - - - - - - - - 2

We would equate equation 1 to equation 2, it becomes

x^2-5x+7 = 2x+1

x^2-5x+7- 2x - 1 = 0

x^2-5x+7- 2x - 1 = 0

x^2 - 5x - 2x + 7 - 1 = 0

x^2 - 7x + 6 = 0

We would use the factorization method of solving quadratic equations.

x^2 - 6x - x + 6 = 0

x(x - 6) - 1(x - 6)

(x - 6)(x - 1) = 0

x - 6 = 0 or x - 1 = 0

x = 6 or x = 1

Substituting both values of x into equation 2, it becomes

For x = 6,

y=2×6 + 1 = 12 + 1 = 13

y = 13

For x = 1,

y=2 × 1 +1 = 2 + 1 = 3

y = 3